Identification of cuproptosis-related genes in chronic apical periodontitis based on bulk and single-cell RNA sequencing analyses and experimental validation - Zhang, Caiyi; Zhao, Jie; Pan, Keqing; Liu, Lingshuang; Jiao, Mengyu; Yuan, Changqing; Wan, Chunyan (Frontiers in Immunology, 2025)
BackgroundChronic apical periodontitis (CAP) is a prevalent oral inflammatory disease, yet the complex mechanisms underlying its etiology remain unclear. A recently identified cell death pathway known as cuproptosis may be linked to this condition.MethodsDifferentially expressed cuproptosis-related genes (DE-CRGs) were identified by integrating human CAP dataset (GSE237398) with health control (HC) dataset (GSE223924) from the Gene Expression Omnibus (GEO) database. Subsequently, single-cell RNA sequencing (scRNA-seq) data from clinical samples with CAP (n=3) and HC (n=3) from the GSE171213 dataset were analyzed to assess variations across different cell clusters. The association of CRGs with macrophages and fibroblasts in periodontitis was then explored. Fibroblasts and macrophages were selected for further analysis, which included subset classification, cell-chat analysis, and functional enrichment analysis. Additionally, Receiver Operating Characteristic (ROC) curves were employed to evaluate the discriminatory ability of gene features. Changes in DE-CRGs within the whole periodontitis tissue were confirmed through quantitative real-time PCR (qRT-PCR) and immumohistochemical staining (IHC).ResultsEight CAP-related DE-CRGs were identified through bulk mRNA sequencing. Numerous interactions among these CRGs were observed, highlighting the complexity of protein-protein interactions. ROC curve analysis demonstrated strong diagnostic potential for these genes. ScRNA-seq sequencing revealed significant alterations in CRGs within fibroblasts and macrophages, along with close intercellular communication between these cell clusters. qRT-PCR and IHC analysis of clinical samples further confirmed DE-CRGs expression in CAP.ConclusionThese findings suggest that CRGs are closely associated with the COL4A1-Fibro and APOE-Macro intercellular interactions, which may facilitate the occurrence and progression of cuproptosis in chronic apical periodontitis.